(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 1998)
The issue of why and how people intervene in the housing process influences the appropriateness of housing. The opportunities and constraints in changing the built environment are placed in the context of the need for change and the intend to make changes. However, the involvement of the user to fulfill their need is often affected by social, physical and financial constraint. These are the reasons that encourage the user to modify and improve his living environment to make it congruent with lifestyle. However, the catalysts for the changes are governed by several factors that affect the physical environment in the process as well as the product. In relation to traditional Malay residential environment the hidden dimension of privacy is not only expressed by the physical form of the building. Privacy as one of the attributes of the dwelling is highly valued rather than physically defended. Although, the word privacy does not exist in the Malay language but the meaning is well understood rather than explicitly explained. With respect to this, the concepts of social structure and culture are examined in order to understand the interrelationship between social and spatial phenomena. Hence, this paper attempts to explore the spatial usage of dwelling of the Malays in relation to the concept of privacy in their daily and seasonal activity. By focusing on these aspects it will help to identify the values the people hold about their living environment.